HOW TEACHERS CHOOSE TRAINING COURSES. EMPIRICAL RESEARCH RESULTS - Ivashnova, Svitlana (Continuing Professional Education: Theory and Practice, 2020)
The article presents the results of a study of individual strategies for choosing training courses by teachers of general secondary education institutions. The article substantiates the choice of research methods and means for processing the results; describes the methodology for preparing an in-depth interview guide, its conduct, and analysis. The experiment results confirmed the interconnection between the level of demonstration of the extrinsic negative element of motivation for professional development and the Yanis coefficient calculated from the data of the content analysis of the in-depth interview. In the process of research, the educational request of teachers, which is mainly focused on updating methods of action, is specified, which indicates (whether conscious or not) the insufficient effectiveness of traditional professional technologies. The identified selection strategies (focusing on the opinion of significant individuals and accounting for characteristics of professional activity) should be considered not only when developing new training courses, but also when promoting them at the educational services market. The research team prepared relevant recommendations for the developers. Based on the results of the study, the methodological recommendations were developed for the system of postgraduate teacher education. The experiment, which is conducted in 22 educational institutions in Kyiv (Ukraine) and covers more than 1,750 teachers, requires verification in other conditions (small schools in remote regions, regional and district centres) since in the program it is not highlighted the impact of the megalopolis on the activity of teachers, and other local factors that may be significant.